Optimum conditions for high-speed solid-liquid separation by ballasted flocculation - Suzuki, Yoshihiro (Water science and technology : a journal of the International Association on Water Pollution Research, 2023)
In the ballasted flocculation, high-speed sedimentation of suspensions is achieved using a microsand as a ballast material and a polymer flocculant combined with microflocs made of polyaluminum chloride (PAC) as an inorganic coagulant. In this study, three turbid water samples containing kaolin clay (kaolin concentration: 20, 200, and 500 mg/L) were treated by coagulation-sedimentation and ballasted flocculation. The effects of pH and PAC dosage, which are the controlling parameters for coagulation, and the microsand (silica sand) and polymer dosages, which are the controlling parameters for ballasted treatment, on the treatment efficiency and floc settling velocity were examined. The floc settling velocity under the optimum conditions was 17 times higher than that of the conventional coagulation-sedimentation process using PAC. The turbidity was 0.54 turbidity unit (TU) (TU as the kaolin standard), and its removal efficiency was 99.7%. Furthermore, turbid water samples with different kaolin concentrations (20 and 500 mg/L) were treated via the ballasted flocculation. In this study, fundamental information on the optimization of each dosage condition of coagulant, ballast, and polymer and pH condition in ballasted flocculation was obtained, and the removal mechanisms under optimal, underoptimistic and overoptimistic conditions were proposed